Prognostic factors and surgical approaches in the analysis of primary central nervous system diffuse large B-cell lymphoma: a large population-based cohort study and external validation - Pan, Zhibo; Huang, Zhaoneng; Xing, Zhenqiu; Yang, Jianjing; Huang, Shengwei; Zhang, Yu (Frontiers in Neurology, 2024)
IntroductionThis study aims to investigate prognostic indicators and assess surgical interventions’ impact on Primary central nervous system lymphoma-diffuse large B-cell lymphoma (PCNS-DLBCL) patients.MethodsA comprehensive examination was performed on a group of 3,962 cases in the Surveillance, Epidemiology, and End Results (SEER) database, as well as 27 cases of PCNS-DLBCL from the First Affiliated Hospital of Wenzhou Medical University. The application of both univariate and multivariate Cox regression analyses facilitated the identification of significant risk factors associated with PCNS-DLBCL. Developing and verifying nomograms, the reliability of the nomogram was evaluated by C-index, ROC curve, calibration curve and decision curve analysis. Finally, by using Kaplan–Meier (KM) curves to assess the survival rates for PCNS-DLBCL patients.ResultsAge, gender, marital status, tumor location, HIV infection status, chemotherapy, and surgical scopes emerged as independent prognostic factors for overall survival (OS) in multivariate Cox regression analysis, whereas gender did not demonstrate significance as a factor for cancer-specific survival (CSS). The C-index, calibration curves, ROC curves, and DCA curves demonstrating strong reliability and practicality. KM analysis revealed significantly improved OS and CSS in patients who underwent surgical resection compared to those who received no surgery/biopsy, especially receiving subtotal resection (STR). In addition, among patients receiving chemotherapy, both STR and gross total resection (GTR) improved survival time compared to chemotherapy alone, particularly with STR. In the non-chemotherapy group, GTR potentially improved CSS, there was no notable disparity in OS between patients who underwent surgery and those who did not or received biopsy.ConclusionThis study analyzed prognostic factors in PCNS-DLBCL patients, resulting in nomograms predicting 1-, 3-, and 5-year OS and CSS, which showed preferable performance. Combining different resection scopes with chemotherapy improved survival compared to chemotherapy alone, advocating for integrated treatment strategies. Surgery alone is not recommended based on our findings.